A trade-off between embolism resistance and bark thickness in conifers: are drought and fire adaptations antagonistic?. (4th May 2018) - Resco de Dios, Víctor; Arteaga, Carles; Hedo, Javier; Gil-Pelegrín, Eustaquio; Voltas, Jordi
ABSTRACT: Background : Understanding the mechanisms that explain the spatial distribution of conifers across biogeographical gradients is important for anticipating potential range shifts owing to global change. Classical explanations have involved trade-offs between shade and drought tolerances, but more recent studies observed that trade-offs between fire and drought tolerances could also be important. Aims : Here we propose that a contributing mechanism to explain how conifer species are distributed across productivity gradients – with marked variation in the incidence of fire – involves a trade-off between allocation to bark, which serves to protect against fire, or to embolism resistance, which serves to protect against drought. Methods : We compiled information from different datasets and performed regression analyses. Results : We observed a trade-off between bark thickness and embolism resistance in conifer species such that species show either large investments of carbon to the bark or have thinner barks but xylem resistant to embolism; we did not observe conifer species concomitantly showing high fire tolerance and embolism resistance. Conclusions : This study serves as a starting point for a novel framework on how fire and drought adaptations affect conifer biogeography. Additional studies will be necessary to discover the generality of our findings by including other species of conifers, for example those in the Southern Hemisphere.